Prodromal Dementia With Lewy Bodies and Recurrent Panic Attacks as the First Symptom: A Case Report - Jaramillo-Jimenez, Alberto; Ying, Yinbing; Ren, Ping; Xiao, Zhan; Zhang, Qian; Wang, Jian; Rong, Han; Borda, Miguel Germán; Bonanni, Laura; Aarsland, Dag; Wu, Donghui (Frontiers in Neurology, 2022)
Psychiatric-onset dementia with Lewy bodies (DLB) might include depression, hallucinations, anxiety, and apathy symptoms. Here we report a DLB patient with recurrent panic attacks as the first symptom, 5 years before a biological-based diagnosis of probable DLB. We present an extended description of the clinical presentation and course from psychiatric-onset DLB to dementia in an 83-year-old woman. This case illustrates the common misdiagnosis of DLB, as well as the delay before having a detailed clinical and biomarker assessment for structured diagnosis. With a detailed description of the clinical presentation of this case, the empirical treatment strategies, and the patient perspectives, we aim to make aware clinicians of panic attacks within the psychiatric-onset DLB.